Singing to the Plants: A Guide to Mestizo Shamanism in the Upper Amazon - Eisenberg, Amy (Ethnobiology Letters, 2014)
Review of Singing to the Plants: A Guide to Mestizo Shamanism in the Upper Amazon Stephan V. Beyer. University of New Mexico Press, Albuquerque. Pp. 544, 12 halftones, 2 charts. 29.95 (paperback). ISBN 978-0-8263-4370-5.